CONTRIBUTION OF BUTANE GAS TO THE DYNAMISATION OF INTRA-URBAN TRANSPORT IN DALOA - Fulgence , KONAN Amani; François, KACOU N’guessan; Ferdinand, AYENON Séka (IJRDO - Journal of Social Science and Humanities Research, 2022)
Following the period of political instability (from 2000 to 2011) in Côte d'Ivoire, urban traffic in Daloa has been gloomy and is now driven by antiquated taxis equipped with butane gas drums. The laxity of state structures has also encouraged their dependence on artisanal activities of decanting butane gas. Nevertheless, with the recurrent use of this 'gaseous fuel', the maximisation of the financial gains of these promoters of intra-urban transport is achieved to the detriment of the safety of the users' shuttles. The objective of this study is to take a critical look at current intra-urban transport in Daloa. The methodology used is based on documentary research and field observation to gather information and data. The questionnaire survey was carried out through a sample of taxi operators and artisans who illegally deliver butane gas. The semi-structured interview was carried out at the regional directorate of hydrocarbons, the technical directorate of the town hall, and the regional directorate of sanitation and health. Thus, the study notes the disruption of intra-urban transport activities in Daloa due to socio-political unrest. Faced with the difficult renewal of the taxi fleet, the resilience of mass transport promoters has led to a major interest in the gaseous product of B6 and B12 drums, intended for domestic households.